A process for the selective removal of arsenic from contaminated water using acetate functionalized zinc oxide nanomaterials. Issue 4 (10th September 2012) - Singh, Nahar; Singh, S.P.; Gupta, Vinay; Yadav, Harish Kumar; Ahuja, Tarushee; Tripathy, S. Swarupa; Rashmi,
<x xml:space="preserve">Abstract</x> This research article deals with the uptake of arsenic from contaminated water using acetate functionalized zinc oxide (ZnO) nanomaterials. The ZnO nanomaterials of various sizes (6–60 nm) have been synthesized following different wet chemical routes. The arsenic removal efficacy of acetate functionalized ZnO nanomaterials was carried out at different pH and time interval. It has been concluded from the study that ZnO nanomaterials (<60 nm) prepared by zinc acetate precursor effectively removes arsenic, while ZnO of same size prepared from zinc chloride, zinc nitrate, zinc sulphate precursor could not remove arsenic considerably. However, ZnO of same size synthesized using other than zinc acetate precursor and functionalized with acetate ions removes arsenic effectively. It is also proposed that acetate ions over the surface of ZnO adsorb arsenic by an oxo‐coordination mechanism and purifies water up to permissible limits of arsenic at pH 5.8–6.8. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 1023–1029, 2013